Comparison of Antibodies for Immunohistochemistry-based Detection of HER3 in Breast Cancer. Issue 3 (March 2018) - Luhtala, Satu; Staff, Synnöve; Barok, Mark; Tanner, Minna; Isola, Jorma
Abstract : Background: Growth factor receptor HER3 ( ErbB3 ) lacks standardized immunohistochemistry (IHC)-based methods for formalin-fixed paraffin-embedded (FFPE) tissue samples. We compared 4 different anti-HER3 antibodies to explain the differences found in the staining results reported in the literature. Materials and Methods: Four commercial HER3 antibodies were tested on FFPE samples including mouse monoclonal antibody clones, DAK-H3-IC and RTJ1, rabbit monoclonal antibody clone SP71, and rabbit polyclonal antibody (SAB4500793). Membranous and cytoplasmic staining patterns were analyzed and scored as 0, 1+, or 2+ according to the intensity of the staining and completeness of membranous and cytoplasmic staining. A large collection of HER2-amplified breast cancers (n=177) was stained with the best performing HER3 antibody. The breast cancer cell line, MDA-453, and human prostate tissue were used as positive controls. IHC results were confirmed by analysis of flow cytometry performed on breast cancer cell lines. Staining results of FFPE samples were compared with samples fixed with an epitope-sensitive fixative (PAXgene). Results: Clear circumferential cell membrane staining was found only with the HER3 antibody clone DAK-H3-IC. Other antibodies (RTJ1, SP71, and polyclonal) yielded uncertain and nonreproducible staining results. In addition to cell membrane staining, DAK-H3-IC was also localized to the cytoplasm, but no nuclear staining was observed. In HER2 -amplified breast cancers, 80% of samples were classified as 1+ or 2+ according to the HER3 staining on the cell membrane. The results from FFPE cell line samples were comparable to those obtained from unfixed cells in flow cytometry. IHC conducted on FFPE samples and on PAXgene-fixed samples showed equivalent results. Conclusions: We conclude that IHC with the monoclonal antibody, DAK-H3-IC, on FFPE samples is a reliable staining method for use in translational research. Assessment of membranous HER3 expression may be clinically relevant in selecting patients who may most benefit from pertuzumab or other novel anti-HER3 therapies. Abstract : Supplemental Digital Content is available in the text.